Parkia biglobosa (Mimosaceae): Botany, Uses, Phytochemical Properties and Pharmacological Potential - Collen Musara ,; Elizabeth Bosede Aladejana ,; Silas M. Mudyiwa ,; Charles Karavina, (Journal of Pharmacy and Nutrition Sciences, 2020)
Parkia biglobosa (Jacq.) R. Br. ex G. Don, popularly known as the African locust bean tree, is a perennial tree legume that belongs to Mimosoïdeae sub-family and family of Fabaceae. This study is aimed at reviewing the botany, nutritional uses, phytochemical and pharmacological properties of P. biglobosa and the information was undertaken using electronic databases such as Scopus, Google Scholar, Elsevier, Science Direct, Web of Science, Pubmed, SciFinder, BMC and Open-thesis. Parkia biglobosa is a very important multipurpose tree that is used essentially for food, medicinal, cultural, economic and magico-therapeutic purposes. Due to its socio-economic and cultural importance, P. biglobosa species are vulnerable to unsustainable harvesting and are declining in numbers because they remain semi- or undomesticated in some west Africa countries. Different aqueous and organic extracts of P. biglobosa indicate that the species are rich in saponins, tannins, flavonoids, resins, carbohydrates, terpenoids, phenols, sterols, and cardiac glycosides. The nutritional and pharmacological benefits of P. biglobosa has been associated with its physicochemical properties. Pharmacological studies on P. biglobosa exhibited antimalarial, anti-helminthic, antibacterial, antidiabetic, antihypertensive, anti-inflammatory, analgesic, anti-carcinogenic, anti-trypanosomic activities and antioxidant properties. Threats to the survival of this multipurpose species are also highlighted.